Case 3516: Scapsipedus micado Saussure, 1877 (currently Velarifictorus micado; Orthoptera, Gryllidae): proposed conservation of usage of the specific name by the designation of a neotype - Heads, Sam W; Ichikawa, Akihiko (Bulletin of Zoological Nomenclature)
(Acknowledgement of receipt published in BZN 67 (1): 2; Case not published). Following correspondence with the authors, the Case is now closed